2018
DOI: 10.1017/ice.2018.191
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter investigation to characterize the risk for pathogen transmission from healthcare facility sinks

Abstract: In 4 hospitals, we demonstrated frequent dispersal of fluorescent tracer and fluoroquinolone-resistant gram-negative bacilli from sink drains to sink bowls and to surfaces outside the bowl. Fluorescent tracer dispersal correlated inversely with the depth of the sink bowl. Modifications in sink design could substantially reduce the risk for pathogen dissemination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 7 publications
(16 reference statements)
1
12
0
Order By: Relevance
“…9,10 Moreover, organisms colonizing sink drains can be dispersed from beneath the strainer to the sink bowl, and countertop, and to patients or personnel by splashing of flowing water. [11][12][13] Unfortunately, addressing sink contamination is challenging because sink drains are not amenable to cleaning and disinfection. 14 For example, sinks in healthcare facilities typically have fixed, narrow strainer holes that do not permit access by brushes that could be used to remove bioburden prior to application of disinfectants.…”
mentioning
confidence: 99%
“…9,10 Moreover, organisms colonizing sink drains can be dispersed from beneath the strainer to the sink bowl, and countertop, and to patients or personnel by splashing of flowing water. [11][12][13] Unfortunately, addressing sink contamination is challenging because sink drains are not amenable to cleaning and disinfection. 14 For example, sinks in healthcare facilities typically have fixed, narrow strainer holes that do not permit access by brushes that could be used to remove bioburden prior to application of disinfectants.…”
mentioning
confidence: 99%
“…However, similar dispersal of gram-negative bacilli has been demonstrated in sinks in 4 hospitals. 10 The sink drain cover was only tested for 1 hand-washing episode per sink. However, we previously implemented the devices for a 2-week period in an intensive care unit and demonstrated that organisms in the sink bowl can be dispersed by flowing water.…”
Section: Discussionmentioning
confidence: 99%
“…Of these characteristics, only sink bowl depth was associated with dispersion of the gel outside the bowl, with dispersion occurring in nearly half of sinks with depth ≤19 cm and rarely when depth exceeded 24 cm. 8 Additionally, there are important dynamics between water flow rate and pathogen dispersion that may not be fully mediated by sink design and must be balanced with functionality and the risks of low-flow states.…”
Section: Sink Designmentioning
confidence: 99%
“…At our institution, we documented transmission of KPC-producing Citrobacter freundii from a colonized in-room sink P trap and drain to the sink edge during routine use of the sink (Lewis and Smith, unpublished data). Factors including sink design, water flow rates 8 and degree of drain colonization all influence the degree of pathogen transmission from sink drains.…”
Section: Sinks As Sources Of Transmission Of Multidrug-resistant Orgamentioning
confidence: 99%
See 1 more Smart Citation